Between capital and land : the Jewish National Fund's finances and land-purchase priorities in Palestine, 1939-45 - Tuten, Eric Engel (RoutledgeCurzon, 2005)
Tuten shows how the Jewish National Fund (JNF) proved to be flexible in its fundraising to obtain its land-purchase objectives during the Second World War. He provides a detailed examination of the Jewish National Fund's internal development and analyses the relationship between JNF's finances and land purchase priorities. A valuable addition to recent re-evaluations of Israeli history and institutions, this book will be of interest to those researching Palestinian history, Jewish and Israeli history and the history of the modern Middle East.
Keywords: Jewish National Fund -- Finance.; Jewish National Fund; Land settlement -- Palestine -- History -- 20th century.; Palestine -- Colonization -- History -- 20th century.; Palestine -- History -- 1917-1948.; Colonisation intérieure -- Palestine -- Histoire -- 20e siècle.; Palestine -- Histoire -- 1917-1948.; BUSINESS & ECONOMICS -- Real Estate -- General.; Colonization; Finance; Land settlement; Middle East -- Palestine; 1900-1999; Electronic books.; History